Variability Result Induction Of Ionization By Gamma Cobalt-60 Ray - Wahlia Fullah Fina (Universitas Airlangga, 2019)
ABSTRACTThe research was conducted to study the effect of 60Co gamma irradiation to the growth of adenium (Apocynaceae sp.) and to findout the effective dose of gamma 60Co irradiation to adenium (Apocynaceae sp.). The research was designed using Completely Randomized Post Design with 5 groups of treatment and 4 replicants for every treatment with variation of irradiating dose 2, 6, 12 dan 20 gray, all treatment were observed every 3 weeks until 12 weeks. The growth of adenium (Apocynaceae sp.) : biomassa, high of crop and the number of leaf was analyzed by ANAVA and followed by Tuckey (Honestly Significant Difference) with α = 0,05% for high and dry weight crop, while the number of leaf were analyzed with Kruskal-Wallis with α = 0,05%, then was analyzed with regression test. The Results showed that the irradiating caused influence the increased of biomassa and high of adenium (Apocynaceae sp.) crop significantly at observation of week 3, 9 and 12. For number of leaf, irradiating dose giving no significant influence. The optimum doses of 60Co gamma irradiation for the growth of biomassa and high of adenium (Apocynaceae sp.) crop at observation of week 3, 9, and 12 were 6 gray. Keyword : 60Co, gamma irradiation, adenium (Apocynaceae sp.).